Pengaruh Kompensasi, Lingkungan Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Rumah Sakit Bhayangkara Kendari - Lili Yanti; Nurwati Nurwati; Aidin Hudani Awasinombu; Dedy Takdir Syaifuddin; Nursaban Rommy Suleman; Asrip Putera (Pascasarjana Universitas Halu Oleo, 2023)
This study was conducted with the aim of testing and explaining the effect of compensation, work environment and job satisfaction on employee performance at Bhayangkara Kendari Hospital. This type of research is a quantitative approach with explanatory research. The population in the study were all employees of the Bhayangkara Kendari Hospital, totaling 60 employees, not including the leadership. the sampling technique was carried out randomly based on strata (stratified proportional random sampling, meaning that the object of research was all employees of Bhayangkara Kendari Hospital. Analysis using structural equation modeling (SEM) using the SmartPLS version 3.2 program packageThe results of this study indicate that compensation has a positive and significant effect on employee performance at Bhayangkara Kendari Hospital. The direction of the influence of this relationship is positive, which means that the better the compensation, the better the performance of the Bhayangkara Kendari Hospital employees. The work environment has a positive and significant effect on the performance of employees at Bhayangkara Kendari Hospital. The direction of the influence of this relationship is positive, which means that the better the work environment, the better the performance of Bhayangkara Kendari Hospital employees and job satisfaction has a positive and significant effect on the performance of Bhayangkara Kendari Hospital employees. The direction of the influence of this relationship is positive, which means that the better job satisfaction, the performance of Bhayangkara Kendari Hospital employees will also be better.